A Critical Reading of Christian Peacemaker Teams' International Accompaniment and Solidarity Work Through a Peace and Conflict Studies Lens. Issue 3 (3rd July 2018) - Hrynkow, Christopher
Abstract: Christian Peacemakers Teams is an interfaith coalition of action that undertakes international accompaniment and solidarity work with local partners. This article employs a Peace and Conflict Studies lens, to map and analyze that faith-inspired work from its conceptual formation within Anabaptist traditions to its present-day ecumenical configuration. Through this approach, tensions and promises of both Christian Peacemakers Teams work and a Peace and Conflict Studies perspective are made clearer. In the process, this article highlights an instance of faith-based diplomacy that mostly travels along a different, more grassroots track, than the one most frequently considered by Political Science scholars.